2013
DOI: 10.3810/psm.2013.09.2023
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Management of Patellofemoral Pain Syndrome

Abstract: A large number of athletes are impacted by PFPS every year, particularly young runners. Sports medicine researchers have investigated many possible therapies for patients with PFPS; however, no clear guidelines have emerged regarding the management of the syndrome. Our review analyzes recent literature on PFPS and identifies specific treatment recommendations. The most effective and strongly supported treatment modality for patients with PFPS is a combined physiotherapy program, including strength training of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 39 publications
3
35
0
1
Order By: Relevance
“…Despite the lack of meta-analyses on this subject, literature reviews on the issue corroborate the findings of the present study (16,27,28).…”
Section: Discussionsupporting
confidence: 80%
“…Despite the lack of meta-analyses on this subject, literature reviews on the issue corroborate the findings of the present study (16,27,28).…”
Section: Discussionsupporting
confidence: 80%
“…Physiotherapy is the first-line option for beginning conservative treatment, and has been shown to be highly effective. 2 Unfortunately, in a small subset of patients, conservative management will fail, as it did in both of these patients. This leaves us with the predicament of what to do with the patient who has failed evidence-based, conservative treatment.…”
Section: Discussionmentioning
confidence: 98%
“…While there have been procedures used for the treatment of PFPS, previous research has shown that surgical techniques have been ineffective. 2 The surgeon responsible in these two cases was faced with two patients who had been suffering significant pain for a long time. These were both young patients who were limited in their activities by the pain, to the point that they were willing to go to great lengths for relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes open communication between the orthopedist, the physical therapy team and the patient. Several investigators have identified a link between abnormal hip strength and patellofemoral pain [10][11][12]26,27]. Excessive hip adduction and internal rotation can cause a decrease in the contact area between the patella and trochlea and a subsequent increase in the lateral joint stress [28][29][30].…”
Section: Discussionmentioning
confidence: 99%